INFLUENCE OF LEADERSHIP, MOTIVATION, DISCIPLINE AND COMPETENCE ON APARATURE PERFORMANCE IN SIMPANG MAMPLAM SUB-DISTRICT OFFICE, BIREUEN DISTRICT ACEH PROVINCE - M.; Marwan; Mursyidi (LPPM-UNIKI, 2020)
The study was conducted on 125 offices of SimpangMamplam District Bireuen Regency. With the aim of knowing and measuring 1) the influence of leadership on the performance of the Apparatus, 2). the influence of motivation on the performance of the Apparatus, 3). the effect of the work discipline on the performance of the Apparatus, and 4). the effect of competence on the performance of the Apparatus. The research method used is a quantitative verification approach, with a path analysis method. Descriptively, the results of the study showed that there was support from the Camat Leadership on performance reaching 79.68 percent, this should be optimized again so that employees received clear directions and the Camat's concern for the performance of its employees. Likewise from work motivation, work discipline, and employee competency factors. It appears that the motivation of new employees reached 69.70 percent, while the level of employee discipline reached 74.65 percent. but the level of competence has only reached 70 percent. The results of the path analysis, with a 95 percent confidence level, the results show that 1). There is an influence of aspects of the Camat Leadership to improve employee performance, both direct influence and indirect influence through work motivation, work discipline, and competency support owned by employees, by 19.98 percent. 2) there is a significant influence between motivation and performance by 21.03 percent.3). While the influence of employee discipline on employee performance, both the direct contribution of factors, as well as the relationship with motivation support, employee competence, and Camat Leader-ship, amounted to 16.84%. 4) And competency factor which is no less important factor that must be owned by employees contributes to the improvement of the performance of Simpang Mamplam District Office staff in the Bireuen Regency by 18.35 percent. The coefficient of determination (R2) of 0.578 explains that the contribution of aspects of camat leadership, work motivation, work discipline and employee competence to Performance amounted to 57.8%.